Determination of Firm Value on Cost Leadership Strategy, Executive Compensation and Foreign Ownership in the Health Sector of Indonesian Public Listed Companies - Majidah; Hilwa Ramadhanti Sakina (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2023)
Investors' perception of how well a company manages resources, indicated by its share price, is known as company value. Referring to signaling theory, cost leadership strategy, executive compensation and foreign ownership give positive signals on the value of the company. Meanwhile, executive compensation as per agency theory is expected to be able to suppress agency problems, so as to produce quality performance so that investors respond positively. This study aims to examine cost leadership strategy, executive compensation, foreign ownership, and enterprise risk management as determinants of corporate value. Health sector companies listed on the Indonesia Stock Exchange in 2017-2021 became the population of this study. Purposive sampling obtained 54 observational data. Data analysis using panel data regression. The results explain that cost leadership strategy, executive compensation, foreign ownership, and enterprise risk management are simultaneously determinants of company value. Cost leadership strategy and executive compensation are partial determinants of a company's value.  However, foreign ownership is a negative determinant of corporate value in the health sector on the IDX, the findings are new to this study.